2005
DOI: 10.1007/s10867-005-6732-6
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of Red Blood Cells and Rouleaux Disaggregation in Interference Laser Fields

Abstract: Abstract. The effect of interference laser fields on red blood cells (RBCs) was investigated both theoretically and experimentally. The optical trapping and orientation of individual RBC in interference fringes were observed. It was found that RBC rouleaux undergo disaggregation under the action of interference laser fields. To describe the effect of RBC orientation in interference fringes, we used the equation for torque exerted on a discoid dielectric particle in a gradient light field. The experimental resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…12 The photobiomodulation effect induced by low power lasers is related to the monochromatic and collimated characteristics of laser beams, 13 which allow photon absorption by a specific photoacceptor 14 This effect has been reported to accelerate tissue repair and analgesia. 15,16 Also, photobiomodulation has been described in cells associated with inflammatory response and tissue repair, such as lymphocytes, 17 fibroblasts, 18 macrophages, 19 in the movement of red blood cells, 20 as well as in blood plasma components, such as hemoglobin, immunoglobulins and proteins, 21 cell growth factors 22 and cytokines. 23 Although therapeutic protocols have been used successfully, the mechanism of action of photobiomodulation has not been understood.…”
Section: Introductionmentioning
confidence: 99%
“…12 The photobiomodulation effect induced by low power lasers is related to the monochromatic and collimated characteristics of laser beams, 13 which allow photon absorption by a specific photoacceptor 14 This effect has been reported to accelerate tissue repair and analgesia. 15,16 Also, photobiomodulation has been described in cells associated with inflammatory response and tissue repair, such as lymphocytes, 17 fibroblasts, 18 macrophages, 19 in the movement of red blood cells, 20 as well as in blood plasma components, such as hemoglobin, immunoglobulins and proteins, 21 cell growth factors 22 and cytokines. 23 Although therapeutic protocols have been used successfully, the mechanism of action of photobiomodulation has not been understood.…”
Section: Introductionmentioning
confidence: 99%
“…LBI is a promising technology for the volume creation of a large regular array of optical traps with easily constructed and inexpensive lenses. This method does not require strongly focused beams and provides a way to generate periodical and quasi-periodical optical traps with adjustable periods and less damaging, so that simultaneous spatial manipulation of a large number of particles can be achieved [10]. However, compared with the current approaches, most of studies for the creation of multiple optical traps are limited to only create a pattern of linear interference fringes or a few of dot traps without the adjustment of the formation.…”
Section: Introductionmentioning
confidence: 99%
“…Drochon [8] obtained the relationship between the RBC velocity and deformed shape under different flow strengths, suspending medium viscosity and cell membrane elasticity using the cell transit analyzer. Kruchenok et al [9] observed the orientation of individual RBCs in interference fringes and found that RBC rouleaux undergo disaggregation under the action of interference laser fields. Lima et al [10] measured velocity distribution of RBC suspension flow in a microchannel with a 0.1 × 0.1 mm 2 cross-section by confocal micro-PIV.…”
Section: Introductionmentioning
confidence: 99%